PENERAPAN GOOD CORPORATE GOVERNANCE BERBASIS FILOSOFI HAMEMAYU HAYUNING BAWANA SEBAGAI SOLUSI PENGUATAN TATA KELOLA PERUSAHAAN - Wanda Dwi Ramadhan; Edy Sukarno (Publika Citra Media, 2026)
This study examines the integration of Good Corporate Governance (GCG) principles with the local philosophy of Hamemayu Hayuning Bawana as an alternative approach to strengthening corporate governance in Indonesia. This philosophy emphasizes the balance between human values, environmental sustainability, and moral responsibility, which conceptually aligns with core GCG principles such as transparency, accountability, responsibility, independence, and fairness. Using a qualitative case study approach in a manufacturing company in Gresik, this research explores how local cultural values are embedded in governance practices. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings reveal that the integration of Hamemayu Hayuning Bawana contributes to strengthening governance practices, particularly in enhancing ethical awareness, social responsibility, and stakeholder relationships. However, the study also identifies gaps between formal governance mechanisms and their practical implementation, especially in aspects of accountability, fairness, and independence. Furthermore, the results indicate that the incorporation of local cultural values provides a contextual governance approach that supports organizational sustainability, yet faces challenges in adapting to modern business dynamics driven by globalization and technological change. This study contributes to the literature by offering a culturally grounded perspective on GCG and highlighting the importance of aligning formal governance systems with local ethical values. Practical implications are provided for organizations seeking to develop more inclusive, transparent, and sustainable governance systems.